FITNESS PRACTICE: THE PHYSICAL AND PSYCHOEMOTIONAL STATE - Dekhkonboeva Zulayxo Dilshod (Proximus Journal Publishing, 2024)
The author reveals the importance of fitness training in improving the body. Fitness for women includes a range of specially designed exercises that contribute to the change not only physical but also psychological state. Analysis of the reasons for the interest of many peoples in fitness clubs indicates dissatisfaction with their figure due to excess subcutaneous fat mass. For this reason, many women 18–25 years old prefer to do exercises with aerobic exercise, because it is in this mode of load after the required time actively split fats, and few people pay attention to the state of the muscular system, the weak development of which affects the physical fitness of women and, accordingly, their performance at work, and when performing household chores. If we consider the effectiveness, each direction (strength or aerobic training) brings excellent results
Keywords: fitness; fitness training; fitness and health